2019
DOI: 10.1537/ase.190415
|View full text |Cite
|
Sign up to set email alerts
|

Late Jomon male and female genome sequences from the Funadomari site in Hokkaido, Japan

Abstract: The Funadomari Jomon people were hunter-gatherers living on Rebun Island, Hokkaido, Japan c. 3500-3800 years ago. In this study, we determined the high-depth and low-depth nuclear genome sequences from a Funadomari Jomon female (F23) and male (F5), respectively. We genotyped the nuclear DNA of F23 and determined the human leukocyte antigen (HLA) class-I genotypes and the phenotypic traits. Moreover, a pathogenic mutation in the CPT1A gene was identified in both F23 and F5. The mutation provides metabolic advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
122
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(141 citation statements)
references
References 126 publications
(159 reference statements)
11
122
3
1
Order By: Relevance
“…2-5) in agreement with previous studies [8,9,19]. In the previous studies, it has been indicated that the Jomon people are genetically closer to the Ryukyuans than to the mainland Japanese [3,4]. In other words, the mainland Japanese are genetically closer to the Yayoi immigrants from continental East Asia than the Ryukyuans are.…”
Section: Discussionsupporting
confidence: 91%
“…2-5) in agreement with previous studies [8,9,19]. In the previous studies, it has been indicated that the Jomon people are genetically closer to the Ryukyuans than to the mainland Japanese [3,4]. In other words, the mainland Japanese are genetically closer to the Yayoi immigrants from continental East Asia than the Ryukyuans are.…”
Section: Discussionsupporting
confidence: 91%
“…Ancient Taiwan groups and Austronesian-speakers share significantly more alleles with Tai-Kadai speakers in southern mainland China and in Hainan Island 42 than they do with other East Asians (Table S8), consistent with the hypothesis that ancient populations related to present-day Tai-Kadai speakers are the source for the spread of agriculture to Taiwan island around 5000 years ago 43 . The Jomon share alleles at an elevated rate with ancient Taiwan individuals and Ami/Atayal as measured by statistics of the form f 4 (Jomon, Mbuti; Ancient Taiwan/Austronesian-speaker, other Asians) compared with other East Asian groups, with the exception of groups in the Amur Basin Cluster (Table S8) 44 .…”
mentioning
confidence: 99%
“…Haplogroup N9b is represented mainly by lineages of four major subhaplogroups: N9b1, N9b2, N9b3, and N9b4 [34][35][36]. We identified a novel N9b1 mitogenome (MH807371) in one individual from Primorye (Agzu), hence expanding the established geographical scope of the N9b1 haplogroup and disclosing a link between a component of the Udegey ancestry and the Hokkaido Jomon from Japan [36][37][38]. The second prevalent haplogroup is M7a2a3a, which was detected in 8/46 (17.4%) of the Udegey samples (Table 1, Additional file 7: Figure S6).…”
Section: Haplogroups N9b and M7a2mentioning
confidence: 78%